Carbon Credit: a Case Study at the NovaGerar Company - Segreti, João Bosco; Bito, Nelson Satio (Review of Business Management, 2007)
The Kyoto Protocol, signed on December 1977, is an important instrument for reducing greenhouse gas emissions and for pursuing sustainable development. The developed countries that adhered to the Protocol committed themselves to reduce their gas emissions by 5.2% (data-base 1990) during the 2008-2012 period. Of the three modalities for diminishing gas reduction investment costs, this article aims at studying the Carbon Credit instrument foreseen in the Clean Development Mechanism – CDM, which has been designed for handling environmental issues by developing countries, whereby projects that bring positive results are implemented. The purpose of this article is to study the NovaGerar Project developed in Nova Iguaçu – RJ, seeking to investigate if the Carbon Credit incentives provided in the CDM contributes to the project’s economic feasibility, thereby reducing the environmental impacts by reducing greenhouse gases. The analysis of the data showed that the project was not feasible when the analysis focused only on generating electric energy. By adding the Carbon Credit, the project proved to be attractive with an expressive internal rate of return of 36.19% per annum. Key-words: Kyoto protocol. Clean development mechanism – CDM. Carbon credit.